Case report: Spontaneous arterial bleeding in the lateral thoracic region during helmet CPAP treatment: a report of three cases in patients with severe COVID-19 - Tripodi, Vincenzo Francesco; Sardo, Salvatore; Silipigni, Salvatore; Stagno, Alberto; Neri, Antonio Francesco; Bottari, Antonio; Mazzeo, Anna Teresa (Frontiers in Medicine, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has put enormous pressure on healthcare systems worldwide. While the majority of severe cases present with respiratory failure, thrombosis or bleeding have also been reported at unusual sites. Major bleeding, particularly in patients treated with therapeutic anticoagulation, has been observed between the second and third week after the onset of SARS-CoV-2 infection. This article describes three cases of patients admitted to the hospital with severe SARS-CoV-2 pneumonia who had spontaneous arterial bleeding from the thoracic and subscapular regions during treatment with helmet continuous positive airway pressure (H-CPAP) in the intensive care unit (ICU), requiring a percutaneous embolization procedure. A possible correlation with helmet-supported ventilation is hypothesized.